Differentiation of Retinal Organoids from Human Pluripotent Stem Cells. (31st July 2019) - Chichagova, Valeria; Dorgau, Birthe; Felemban, Majed; Georgiou, Maria; Armstrong, Lyle; Lako, Majlinda
Abstract: This unit describes a protocol for generating retinal organoids that contain all major retinal cell types and are responsive to light from human pluripotent stem cells (hPSCs). hPSCs are differentiated in 96‐well plates to allow large‐scale production of organoids that could be used for multiple applications, including study of human retinal development, disease modeling, and compound screening. The differentiation approach is based on the knowledge that insulin‐like growth factor 1 signaling together with retinoic acid and triiodothyronine is important for retinal development. After 22 weeks in culture, the organoids form a thick layer of neuroepithelium containing photoreceptors and bipolar, horizontal, amacrine, Müller, and retinal ganglion cells. Differentiation progress can be tracked by morphological observations and protein localization, as detected with immunocytochemistry. © 2019 by John Wiley & Sons, Inc.